Gymnemic Acids Inhibit Adhesive Nanofibrillar Mediated Streptococcus gordonii–Candida albicans Mono-Species and Dual-Species Biofilms - Veerapandian, Raja; Vediyappan, Govindsamy (Frontiers in Microbiology, 2019)
Dental caries and periodontitis are the most common oral disease of all age groups, affecting billions of people worldwide. These oral diseases are mostly associated with microbial biofilms in the oral cavity. Streptococcus gordonii, an early tooth colonizing bacterium and Candida albicans, an opportunistic pathogenic fungus, are the two abundant oral microbes that form mixed biofilms with augmented virulence, affecting oral health negatively. Understanding the molecular mechanisms of the pathogen interactions and identifying nontoxic compounds that block the growth of biofilms are important steps in the development of effective therapeutic approaches. In this in vitro study we report the inhibition of mono-species or dual-species biofilms of S. gordonii and C. albicans, and decreased levels of biofilm extracellular DNA (eDNA), when biofilms were grown in the presence of gymnemic acids (GAs), a nontoxic small molecule inhibitor of fungal hyphae. Scanning electron microscopic images of biofilms on saliva-coated hydroxyapatite (sHA) surfaces revealed attachment of S. gordonii cells to C. albicans hyphae and to sHA surfaces via nanofibrils only in the untreated control but not in the GAs-treated biofilms. Interestingly, C. albicans produced fibrillar adhesive structures from hyphae when grown with S. gordonii as a mixed biofilm; addition of GAs abrogated the nanofibrils and reduced the growth of both hyphae and the biofilm. To our knowledge, this is a first report that C. albicans produces adhesive fibrils from hyphae in response to S. gordonii mixed biofilm growth. Semi-quantitative PCR of selected genes related to biofilms from both microbes showed differential expression in control vs treated biofilms. Further, GAs inhibited the activity of recombinant S. gordonii glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Taken together, our results suggest that S. gordonii stimulates expression of adhesive materials in C. albicans by direct interaction and or signaling, and the adhesive material expression can be inhibited by GAs.